Simulasi Sistem Monitoring Kenaikan Level Air pada Area Rawan Banjir Secara Real-Time berbasis Smartphone Android - Rasmila, Rasmila; Parhan, Muhammad Rangga; Hadinta, Novri; Putra, M. Soekarno (Jurnal Pengembangan Sistem Informasi dan Informatika, 2024)
Abstract Flooding is the most prevalent disaster that often occurs, flooding occurs due to an increase in water levels in flood-prone areas such as rivers, creeks, swamps and seas that can no longer be dammed which results in overflowing water, in controlling the increase in water levels, a technology is needed that is able to minimize casualties and property. So, the purpose of this research is to create a technology or monitoring tool for water level rise that can be monitored through an Android smartphone where the use of this system will make it easier for the community and local authorities to monitor real-time water level rise. This research uses Research and Development (R&D) research methodology and data is managed and taken through observation, literature study and validation methods. This system uses the HCSR-04 ultrasonic sensor as a sensor and ESP32 as a microcontroller, as an output result, the data will be in the form of two visualizations, namely real-time graphs and tables and notifications via email. The results of the tool system output are built based on progressive web app through Laravel PHP.